(untitled) (CIPEEX, 2026)
Severe obesity and depression are highly prevalent, bidirectionally interconnected chronic conditions, in which obesity increases the risk of depressive symptoms and depression promotes weight gain, creating a complex cycle. This integrative review analyzes ten studies published between 2020 and 2025, encompassing clinical trials, observational studies, and prospective studies investigating nutritional, behavioral, and integrated interventions. The results show that strategies such as restrictive diets, intermittent fasting, prebiotic supplementation, and combined programs of nutritional re-education, physical activity, and psychological support promote weight loss and, in some cases, improvement in depressive symptoms, although the effects on mood and quality of life remain heterogeneous. Thus, an association between obesity and depression must be understood as multifactorial, requiring integrated, individualized, and sustainable therapeutic approaches to improve clinical outcomes and reduce the impact of these conditions on public health.